Single-channel magnetotactile interface with structurally decoupled polarity–eigenfrequency encoding for in-plane sliding-direction decoding - Xiaojuan Hou; Shaowei Quan; Xin Zhang; Huipeng Zhao; Lin Shi; Fen Li; Wenping Geng; Jian He; Xiujian Chou (Chemical Engineering Journal, 2026)

Dazomet fumigation with black film mulching improves soil microecology, reduces the abundance of antibiotic resistance genes, and increases yield of Panax notoginseng - Yameng Lin; Xiufu Wan; Minghua Li; Tao Meng; Guili Xie; Yuan Liu; Qian Yang; Xiuming Cui; Wenping Zhang; Ye yang (Journal of Environmental Management, 2026)

Patterns and drivers of critical soil moisture threshold across global tree species - Chaoqing Song; Yangyang Fu; Jingyu Yao; Shengnan Chen; Zheng Fu; Shangrong Lin; Jingping Wang; Wenfang Xu; Wenping Yuan (Agricultural and Forest Meteorology, 2026)

Predicting heavy metal distribution coefficient in global soil via machine learning: The effect of mineral heterogeneity - Wenping Zuo; Huangling Gu; Qinpeng Liao; Jin Chao; Chongchong Qi; Junqin Liu; Yuancai Lv; Chen Tian; Zhang Lin (Environmental Research, 2026)

Effects of galactomannan on the quality and component structure of hot-dry noodles during freeze-thaw cycles - Liuyu Wan; Yang Fu; Zhonghua Yuan; Peili Lin; Nian Cheng; Shensheng Xiao; Wenping Ding; Xuedong Wang (Food Chemistry, 2026)

Comparison and application of machine learning, deep learning, and statistical analysis methods in estuarine saltwater intrusion forecasting - Fang Yang; Huazhi Zou; Qi Tang; Lei Zhu; Wenping Gong; Zhongyuan Lin (Journal of Hydrology, 2025)

Modeling two-dimensional soil water–heat–salt transport and cotton growth under strip-film mulched drip irrigation - Dong Lin; Xi Huang; Wenping Bi; Yin Zhao; Xiaomin Mao (Agricultural Systems, 2025)

Evaluating impacts of hydrology and pollution loadings on low dissolved oxygen in an urbanized tidal river network using modeling and monitoring - Heng Zhang; Jiahuan Liu; Tong Li; Siyu Zhang; Zhongyuan Lin; Zhengbo Jia; Wenping Gong; Guang Zhang (Journal of Hydrology, 2025)

Natural factor-based spatial prediction and source apportionment of typical heavy metals in Chinese surface soil: Application of machine learning models - Jin Chao; Huangling Gu; Qinpeng Liao; Wenping Zuo; Chongchong Qi; Junqin Liu; Chen Tian; Zhang Lin (Environmental Pollution, 2025)

Lysosomal cation channel TRPML1 suppression sensitizes acute myeloid leukemia cells to chemotherapeutics by inhibiting autophagy - Meifang Dai; Bingqian Lin; Hao Li; Youming Wang; Miaomiao Wu; Yanan Wei; Wenping Zeng; Lili Qu; Chunlei Cang; Xingbing Wang (Molecular and Cellular Biochemistry, 2025)

Study on substrates purification effect and microbial community structure of vertical subsurface flow constructed wetland under siphon effect - Cheng Jiang; Lin Qiu; Hao Wu; Yong Liu; Fahui Nie; Qinliang Jiang; Wenping Cao (Journal of Water Process Engineering, 2024)

Mapping global distributions of clay-size minerals via soil properties and machine learning techniques - Qinpeng Liao; Huangling Gu; Chongchong Qi; Jin Chao; Wenping Zuo; Junqin Liu; Chen Tian; Zhang Lin (Science of The Total Environment, 2024)

Automated counting and classifying Daphnia magna using machine vision - Yang Ma; Wenping Xiao; Jinguo Wang; Xiang Kuang; Rongqin Mo; Yanfang He; Jianfeng Feng; Hengling Wei; Liwen Zheng; Yufei Li; Peixin Liu; Hao He; et al. (Aquatic Toxicology, 2024)

A leaf age‐dependent light use efficiency model for remote sensing the gross primary productivity seasonality over pantropical evergreen broadleaved forests - Jie Tian; Xueqin Yang; Wenping Yuan; Shangrong Lin; Liusheng Han; Yi Zheng; Xiaosheng Xia; Liyang Liu; Mei Wang; Wei Zheng; Lei Fan; Kai Yan; et al. (Global Change Biology, 2024)
Tropical and subtropical evergreen broadleaved forests (TEFs) contribute more than one‐third of terrestrial gross primary productivity (GPP). However, the continental‐scale leaf phenology‐photosynthesis nexus over TEFs is still poorly understood to date. This knowledge gap hinders most light use efficiency (LUE) models from accurately simulating the GPP seasonality in TEFs. Leaf age is the crucial plant trait to link the dynamics of leaf phenology with GPP seasonality. Thus, here we incorporated the seasonal leaf area index of different leaf age cohorts into a widely used LUE model (i.e., EC‐LUE) and proposed a novel leaf age‐dependent LUE model (denoted as LA‐LUE model). At the site level, the LA‐LUE model (average R 2 = .59, average root‐mean‐square error [RMSE] = 1.23 gC m −2 day −1 ) performs better than the EC‐LUE model in simulating the GPP seasonality across the nine TEFs sites (average R 2 = .18; average RMSE = 1.87 gC m −2 day −1 ). At the continental scale, the monthly GPP estimates from the LA‐LUE model are consistent with FLUXCOM GPP data ( R 2 = .80; average RMSE = 1.74 gC m −2 day −1 ), and satellite‐based GPP data retrieved from the global Orbiting Carbon Observatory‐2 (OCO‐2) based solar‐induced chlorophyll fluorescence (SIF) product (GOSIF) ( R 2 = .64; average RMSE = 1.90 gC m −2 day −1 ) and the reconstructed TROPOspheric Monitoring Instrument SIF dataset using machine learning algorithms (RTSIF) ( R 2 = .78; average RMSE = 1.88 gC m −2 day −1 ). Typically, the estimated monthly GPP not only successfully represents the unimodal GPP seasonality near the Tropics of Cancer and Capricorn, but also captures well the bimodal GPP seasonality near the Equator. Overall, this study for the first time integrates the leaf age information into the satellite‐based LUE model and provides a feasible implementation for mapping the continental‐scale GPP seasonality over the entire TEFs.

Upcycling retired Li-ion batteries into high-performance oxygen reduction reaction electrocatalysts in flexible Al-air batteries - Haolin Hu; Yuelin Wang; Yue Xu; Liangxiao Jin; Samuel Jeong; Xinfu Xie; Chengqian Xiong; Bojun Zhou; Wenping Sun; Jialiang Zhang; Xi Lin; Kailong Hu (Chemical Engineering Journal, 2024)

Cotton stalk decomposition with DBD low-temperature plasma: Characteristics and kinetics - Li Li; Wenping Shao; Lulu Zhao; Lin Zhu; Siyi Wang; Xianchun Li (Bioresource Technology, 2024)

Cotton lands induced cooling effect on land surface temperature in Xinjiang, China - Jie Dong; Zhouye Pang; Shangrong Lin; Xiuhong Zhang; Zhenglan Xie; Peiyang Ren; Xiao Zhang; Wenping Yuan (Agricultural and Forest Meteorology, 2024)

Geothermal fluid chemistry and isotope for interpreting the formation of complex geothermal system in the Gonghe Basin, northeastern Tibetan Plateau - Rui Lu; Wenping Xie; Bo Liu; Shengsheng Zhang; Jinshou Zhu; Wenjing Lin (Journal of Hydrology, 2024)

Salt intrusion dynamics in a well-mixed sub-estuary connected to a partially to well-mixed main estuary - Zhongyuan Lin; Guang Zhang; Huazhi Zou; Wenping Gong (Ocean Science, 2024)
Salt intrusion in estuaries has been exacerbated by climate change and human activities. Previous studies have primarily focused on salt intrusion in the mainstem of estuaries, whereas those in sub-estuaries (those that branch off their main estuaries) have received less attention. During an extended La Niña event from 2021 to 2022, a sub-estuary (the East River estuary) alongside the Pearl River estuary, China, experienced severe salt intrusions, posing a threat to the freshwater supply in the surrounding area. Observations revealed that maximum salinities in the main estuary typically preceded spring tides, exhibiting significant asymmetry in salinity rise and fall over a fortnightly timescale. In contrast, in the upstream region of the sub-estuary, the variation in salinity was in phase with that of the tidal range, and the rise and fall of the salinity were more symmetrical. Inspired by these observations, we employed idealized numerical models and analytical solutions to investigate the underlying physics behind these behaviors. It was discovered that under normal dry conditions (with a river discharge of 1500 m3 s−1 at the head of the main estuary), the river–tide interaction and change in horizontal dispersion accounted for the in-phase relationship between the salinity and tidal range in the upstream region of the sub-estuary. Under extremely dry conditions (i.e., a river discharge of 500 m3 s−1 at the head of the main estuary), salinity variations were in phase with those of the tidal range in the middle as well as the upstream region of the sub-estuary. The variation in salinity in the main estuary along with those in salt dispersion and freshwater influx inside the sub-estuary collectively influenced salinity variation in the well-mixed sub-estuary. These findings have important implications for water resource management and salt intrusion prevention in the catchment area.

Climatic limitations on grassland photosynthesis over the Tibetan Plateau shifted from temperature to water - Jiangliu Xie; Gaofei Yin; Dujuan Ma; Rui Chen; Wei Zhao; Qiaoyun Xie; Cong Wang; Shangrong Lin; Wenping Yuan (Science of The Total Environment, 2024)

Multi-protection of zinc anode via employing a natural additive in aqueous zinc ion batteries - He Zheng; Yun Huang; Jie Xiao; Wenping Zeng; Xinpeng Li; Xing Li; Mingshan Wang; Yuanhua Lin (Chemical Engineering Journal, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

Hydrogen-assisted one-pot synthesis of ultrasmall TiC nanoparticles enhancing hydrogen cycling of sodium alanate - Xin Zhang; Yukai Lin; Lingchao Zhang; Zhenguo Huang; Limei Yang; Zhenglong Li; Yaxiong Yang; Mingxia Gao; Wenping Sun; Hongge Pan; Yongfeng Liu (Chemical Engineering Journal, 2023)

Genome-wide association study reveals markers and candidate genes associated with growth in the rice flower carp, an economic fish species of integrated rice-fish culture in China - Hui Luo; Xianhui Pan; Yin Huang; Zhe Li; Hua Ye; Kangqi Zhou; Luting Wen; Junqi Qin; Wenping He; Xuesong Du; Dapeng Wang; Yong Lin (Frontiers in Marine Science, 2023)
The rice flower carp ( Cyprinus carpio ) is an important fish in integrated rice-fishery farming. Here, we performed the first genome-wide association study (GWAS) for seven growth traits (including body mass, total length, body length, body height, body width, caudal-peduncle depth, and eye spacing) in 200 rice flower carp samples using 369,688 high-quality SNPs and 42,225 indels obtained by double-digest genotyping-by-sequencing (ddGBS). The morphometrics of these traits were highly correlated (Pearson’s correlation coefficients = 0.74–0.99, p < 0.001). GWAS detected 15, 5, 4, 26, 7, 16, and 17 loci significant associated (-log10P ≥ 5) with body mass, total length, body length, body width, body height, caudal-peduncle depth, and eye spacing, respectively. Subsequently, within the 50 kb upstream and downstream regions surrounding these significant loci, 38, 19, 18, 20, 52, 27, and 37 candidate genes for the seven growth traits were detected, respectively. Importantly, B6_4352672 and A8_4978825 were significantly associated with more than five growth traits. These results showed loci significantly associated with more than five growth traits will be helpful for future marker-assisted selection (MAS). Interestingly, chromosomes A8 and B25 had many loci significantly associated with growth traits, most of which were shared among multiple growth-related traits. These results indicated that chromosome A8 and B25 may be closely related to growth traits. Our findings not only help understand the genetic architecture of growth traits in fish but facilitate the identification of candidate genes for marker-assisted selection towards breeding faster-growing rice flower carp in the future.

Multi-responsive graphene quantum dots hybrid self-healing structural color hydrogel for information encoding and encryption - Jingye Yan; Guoyi Pan; Wenjing Lin; Zilun Tang; Jieheng Zhang; Jiaxin Li; Wenping Li; Xiaofeng Lin; Hongsheng Luo; Guobin Yi (Chemical Engineering Journal, 2023)

From Initiation to Maintenance: HIV-1 Gp120-induced Neuropathic Pain Exhibits Different Molecular Mechanisms in the Mouse Spinal Cord Via Bioinformatics Analysis Based on RNA Sequencing - Jian Huang; Fei Lin; Yanling Hu; Chris Bloe Bloe; Dan Wang; Wenping Zhang (Journal of Neuroimmune Pharmacology, 2022)

Biases and improvements of the ENSO-East Asian winter monsoon teleconnection in CMIP5 and CMIP6 models - Wenping Jiang; Hainan Gong; Ping Huang; Lin Wang; Gang Huang; Lisuo Hu (Climate Dynamics, 2022)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2022)

GIS-based evaluation of water-inrush risk from coal floor using logistic regression and certainty factor models - Qiqing Wang; Yuxiang Lin; Wenping Li; Xiaoyang Yu; Yong Zhang (Arabian Journal of Geosciences, 2022)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2021)
Summary Fusarium graminearum is an important worldwide pathogen that causes Fusarium head blight in wheat, barley, maize and other grains. LncRNAs play important roles in many biological processes, but little is known about their functions and mechanisms in filamentous fungi. Here, we report that a natural antisense RNA, GzmetE‐AS , is transcribed from the opposite strand of GzmetE . GzmetE encodes a homoserine O ‐acetyltransferase, which is important for sexual development and plant infection. The expression of GzmetE‐AS was increased significantly during the conidiation stage, while GzmetE was upregulated in the late stage of sexual reproduction. Overexpression of GzmetE‐AS inhibited the transcription of GzmetE . In contrast, the expression of GzmetE was significantly increased in GzmetE‐AS transcription termination strain GzmetE‐AS ‐T. Furthermore, GzmetE‐AS ‐T produced more perithecia and facilitated the ascospore discharge, resembling the phenotype of GzmetE overexpressing strains. However, overexpression of GzmetE‐AS in ∆dcl1/2 strain cannot inhibit the expression of GzmetE , and the GzmetE nat‐siRNA is also significantly reduced in ∆dcl1/2 mutant. Taken together, we have identified a novel antisense lncRNA GzmetE‐AS , which is involved in asexual and sexual reproduction by regulating its antisense gene GzmetE through RNAi pathway. Our findings reveal that the lncRNA plays critical roles in the development of F . graminearum .

PTEN-mediated mitophagy and APE1 overexpression protects against cardiac hypoxia/reoxygenation injury - Wenshuai Tang; Deqing Lin; Mingxiang Chen; Zhiping Li; Weimin Zhang; Wenping Hu; Fuping Li (In Vitro Cellular & Developmental Biology - Animal, 2019)

Genomic and Allelic Analyses of Laccase Genes in Sugarcane (Saccharum spontaneum L.) - Wenping Zhang; Jishan Lin; Fei Dong; Qing Ma; Songlin Wu; Xinyi Ma; Mahpara Fatima; Haifeng Jia; Ray Ming (Tropical Plant Biology, 2019)

Identification and Expression Analysis of TCP Genes in Saccharum spontaneum L - Jishan Lin; Mengting Zhu; Mingxing Cai; Wenping Zhang; Mahpara Fatima; Haifeng Jia; Feifei Li; Ray Ming (Tropical Plant Biology, 2019)

Effect of winds and waves on salt intrusion in the Pearl River estuary - Wenping Gong; Zhongyuan Lin; Yunzhen Chen; Zhaoyun Chen; Heng Zhang (Ocean Science, 2018)
Salt intrusion in the Pearl River estuary (PRE) is a dynamic process that is influenced by a range of factors and to date, few studies have examined the effects of winds and waves on salt intrusion in the PRE. We investigate these effects using the Coupled Ocean-Atmosphere-Wave-Sediment Transport (COAWST) modeling system applied to the PRE. After careful validation, the model is used for a series of diagnostic simulations. It is revealed that the local wind considerably strengthens the salt intrusion by lowering the water level in the eastern part of the estuary and increasing the bottom landward flow. The remote wind increases the water mixing on the continental shelf, elevates the water level on the shelf and in the PRE and pumps saltier shelf water into the estuary by Ekman transport. Enhancement of the salt intrusion is comparable between the remote and local winds. Waves decrease the salt intrusion by increasing the water mixing. Sensitivity analysis shows that the axial down-estuary wind, is most efficient in driving increases in salt intrusion via wind straining effect.

Heme oxygenase-1 protects spinal cord neurons from hydrogen peroxide-induced apoptosis via suppression of Cdc42/MLK3/MKK7/JNK3 signaling - Siyuan Wang; Tao Zhang; Zhen Yang; Jianhua Lin; Bin Cai; Qingfeng Ke; Wenbin Lan; Jinxing Shi; Shiqiang Wu; Wenping Lin (Apoptosis, 2017)

Evaluation of Immunosuppressive Activity of Demethylzeylasteral in a Beagle Dog Kidney Transplantation Model - Huimin An; Yu Zhu; Wenping Xu; Yujun Liu; Jianping Zhang; Zongming Lin (Cell Biochemistry and Biophysics, 2015)

Mutation screening of RAD51C in high-risk breast and ovarian cancer families - Wenping Lu; Xianshu Wang; Hongsheng Lin; Noralane M. Lindor; Fergus J. Couch (Familial Cancer, 2012)

Genetic diversities of the giant panda (Ailuropoda melanoleuca) in Wanglang and Baoxing Nature Reserves - Wei He; Ling Lin; Fujun Shen; Wenping Zhang; Zhihe Zhang; Emily King; Bisong Yue (Conservation Genetics, 2008)